External shocks pass-through into selected central and Eastern European countries - Necula, Ciprian; Murarasu, Bogdan; Radu, Alina-Nicoleta; Anghelescu, Cristina; Zaharia, Alina (Technological and Economic Development of Economy, 2022)
The ongoing COVID-19 pandemic put further pressure on the economies, both at individual and global level and, amid already existing vulnerabilities, worsened the economic prospects. As a result of the negative effects of these tensions in tandem with global value chains disruptions, commodities’ prices increased, leading to strong inflationary pressures around the globe. Given possible permanent effects on inflation expectations, it is therefore questionable how fast those prices are to be stabilized. In this context, this paper focuses on a group of 10 European countries, namely Czechia, Hungary, Poland, Romania, France, Germany, Italy, Spain, the Netherlands and the United Kingdom, in the period spanning from 2005 to 2020. By implementing a GVAR model, the study analyses the pass-through of the external shocks stemming mainly from the Euro Area and the US to the CEE region, comparing the responses obtained for these countries with the ones of the developed economies. Considering the strong trade relationships between the analysed countries, the considered transmission channel is the commercial one. The results indicate that a supply shock in the Euro Area has a significant negative impact on the selected CEE countries’ economic growth, the offsetting factors not being strong enough to diminish the response.First published online 11 October 2022